A Robust Valuation Model for Entrepreneurial Ventures - Haim Kedar-Levy (The Journal of Entrepreneurial Finance (JEF), 2013)
Pro forma estimation of financial statements often builds on constant ratios to sales revenue. While constant ratios may be relevant for established firms operating in predictable industries, they yield noninformative and possibly misleading information when applied to new firms, and particularly to technology ventures. Because new firms grow and change rapidly, a robust analysis should be based on intimate familiarity with the specific firm's business plan. This paper presents an alternative approach that links the firm's budget, as derived from its business plan, to pro forma financial statements, and to valuation models. The resulting estimated firm value is less sensitive to exogenous parameter assumptions than other methodologies.
Keywords: G17; G32; L26; M13; 650; Valuation; Business plan; Entrepreneurship; Pro forma financial statements